DC distribution network to enable integration of PV power sources, distributed energy storages and DC loads in future communities : part I - Chen,Yi Peng (Nanyang Technological University, 2021)
Environment and energy issues have always been the major problems in the development of human society. Renewable energy can generate electricity without any pollution, which is the best way to solve the two issues. Solar energy is different from other renewable energies, which do not need the specific environmental and natural resources. It is the most promising and efficient renewable energy source for Singapore; it can widely use in various sectors such as residential, commercial, and industrial buildings. This project going to study the new type of DC microgrid in the photovoltaic (PV) system, analyzing the advantage and disadvantages of using DC microgrids, investigating the application of PV systems in residential, commercial, and industrial buildings in Singapore. It also studied how this DC distribution system performs compared to the traditional AC distribution system in the public circuit networks. The main goal of this project is to investigate and develop a multiple-bus DC distribution network for future communities to increase efficiency and reduce the next generation of distribution networks' cost.